2020
DOI: 10.1111/jfpe.13403
|View full text |Cite
|
Sign up to set email alerts
|

The encapsulation of curcumin by whey protein: Assessment of the stability and bioactivity

Abstract: Aims:The aims of the present work were to encapsulate curcumin in denaturated whey protein isolate and investigate the physicochemical and morphological properties of whey protein isolate-based nanoparticles (WPI-NPs).Methods: Scanning electron microscopy (SEM) was used to investigate the morphological properties of WPI-NPs. The crystalline structure of the developed NPs was evaluated by using an X-ray diffraction technique. Antiradical activity of pure and loaded curcumin was also tested. in vitro release of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 50 publications
2
33
0
Order By: Relevance
“…Curcumin is a polyphenolic compound derived from the ground rhizomes of Curcuma longa L. Curcumin possesses diverse biological effects such as antimicrobial, antioxidant, and anti‐HIV activities (Solghi, Emam‐Djomeh, Fathi, & Farahani, 2020). It also has been reported that this bioactive compound can be used in treating Parkinson's and Alzheimer's patients (Robles‐Almazan et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is a polyphenolic compound derived from the ground rhizomes of Curcuma longa L. Curcumin possesses diverse biological effects such as antimicrobial, antioxidant, and anti‐HIV activities (Solghi, Emam‐Djomeh, Fathi, & Farahani, 2020). It also has been reported that this bioactive compound can be used in treating Parkinson's and Alzheimer's patients (Robles‐Almazan et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Encapsulation is one of the most effective approaches to enhance the water solubility and stability of bioactive compounds (Seyedabadi et al., 2021; Solghi et al, 2020). This process causes the homogenization of ingredients in a solution containing the macromolecules and emulsifiers for the formation of a stable emulsion (Simon‐Brown et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…WPI has also been shown to improve the storage stability of payloads and resistance to oxidation [ 15 ]. The hydrophobic small molecule, curcumin, for example, is quickly degraded at physiological pH and is also sensitive to light [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it exhibits increased stability against oxidation in the presence of protein [ 16 ]. Solghi et al demonstrated a 60% improvement in oxidative stability when curcumin was encapsulated in dWPI nanoparticles [ 15 ].…”
Section: Introductionmentioning
confidence: 99%